LINGKUNGAN PENDIDIKAN ISLAM DALAM PERSPEKTIF HADIS: Analisis Hadis Riwayat Imam Muslim tentang Belajar Bersama - Desi Kurniasari; Komariyah Komariyah; Rusyaid Rusyaid (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2025)
This study aims to highlights the concept of an Islamic educational environment as reflected in the hadith of the Prophet Muhammad SAW on learning together (ta’allum jama’i), as narrated by Imam Muslim. The values contained in these hadith, such as angelic protection, abundant mercy, inner peace (sakinah), and glory in the sight of Allah, are key indicators learning climate. This study uses a qualitative approach through library research by examining various scientific sources, hadith books, and relevant Islamic educational literature. The results of the study show that applying the principles of hadith in an educational environment can create a collaborative, loving, and worship oriented learning atmosphere. Such an environment plays a role in fostering student’s character to be noble, disciplined, and highly spiritually aware. In addition, the hadith also provides practical guidance for educators in creating a conducive and calming learning atmosphere, as well as protecting students from the negative influences of globalization and moral hadith values in the management of the islamic educational environment not only strengthens the scientific dimension but also fostered a balance between reason, heart, and faith as the main foundation of education oriented towards the formation of perfect individuals, namely individuals who are knowledgeable, faithful, and noble, who are able to face global challenges based on strong Islamic values.